Concentrations of F−, Na+, and K+ in Groundwater before and after an Earthquake: A Case Study on Tenerife Island, Spain - Eduardo de Miguel-García; José Francisco Gómez-González (Hydrology, 2024)
Freshwater, vital for life and ecosystems, accounts for only 2.5% of Earth’s water, and is primarily located in polar caps, underground reservoirs, and surface water. Its quality varies due to environmental interactions, especially in groundwater. Tenerife, located in the Canary Islands, Spain, relies mainly on underground aquifers and tunnels capturing 51.6 cubic hectometers annually. Ensuring safe drinking water is a global challenge due to health risks from poor water quality, including diseases and cancer. Fluoride, sodium, and potassium are essential for health, and are mainly derived from groundwater as fluoride ions (F−) and sodium and potassium cations (Na+, K+). However, excessive F−, Na+, and K+ in drinking water is harmful. The World Health Organization limits F− to 1.5 mg/L, Na+ to 8.70 meq/L, and K+ to 0.31 meq/L. Geological, climatic, and human factors control the presence and transport of F−, Na+, and K+ in groundwater. Seismic events can impact water quality, with long-term effects linked to aquifer structure and transient effects from gas and fluid expansion during earthquakes. This study was motivated by a 3.8 mbLg earthquake in Tenerife in 2012, which allowed its impact on groundwater quality, specifically F−, Na+, and K− concentrations, to be examined. Post-earthquake, F− levels alarmingly increased to 8.367 meq/L, while Na+ and K+ showed no significant changes. This research quantifies the influence of earthquakes on increasing F− levels and evaluates F− reduction during low seismic activity, emphasizing the importance of water management on volcanic islands.